Strategi Media Relations Pemerintah Kabupaten Sragen Dalam Mendapatkan Citra Positif - Khotimah, Nurjanah Husnul; , Drs. Joko Sutarso, S.E, M.Si; , Budi Santoso, M.Si (2015)
As the spearhead of government, public relations plays an important role in building and maintaining a positive image. PR communicator directly or indirectly in delivering government policy, and to communicate information to the public. The information presented can be in the form of oral or written, through various kinds of media such as print media, electronic media. The purpose of this study was to determine how the public relations strategy in cooperation with the media in getting a positive image. This study used qualitative methods, the source of data derived from primary and secondary data, and data collection through observation, interviews, and documentation. Aanalisis data used in this research is the analysis method Interraktif (Data collection, data reduction, data presentation, conclusion). The results of this study that the mass media are used in the dissemination of information that a website, Asri Buana LPP radio, print media, outdoor media. Forms of cooperation with the mass media public relations, among others: 1) Press aligned partner, a public relations practitioner should be able to establish a good working partner relationship with the media. 2) Press Conference, a press conference aims to gather the media to discuss if there are issues that are less good in the community by attending local government officials. 3) Press Release, this press release to be one chance to deliver the facts and the views of an organization to a problem lies. 4) media services, local government provides facilities through public relations work space journalist (press room), which meant that journalists can work well when the pass coverage. 5) Coverage of community activities (srawung residents) function for Local Government closer to the people.